Reoperation in Spinal Dysraphism: Does it Help in Reversing the Neurological Deficits? - Maste, Praful Suresh; Lokanath, Yadhu Kasetti; Mahantshetti, Shambhulingappa S. (Journal of neurosciences in rural practice, 2017)
Aims: After initial primary repair by inexperienced hands for the spectrum of pathological conditions in spinal dysraphism (SD), a few percentage of patients present with recurrent symptoms and worsening neurological status especially when primarily pathology is not identified and dealt properly. When the primary intradural tethering element is left untouched, worsening of symptoms is common. In this retrospective study, we tried to analyze the symptomatology, functional outcome at 1–2 months after the second surgery and associated complications. Subjects and Methods: All patients underwent second surgery at author’s institution. Pre and post-operative data were evaluated using Necker –Enfants Malades (NEM) neurological and modified Hoffer ambulatory scale. Results: The main presenting complaints were bladder incontinence and limb weakness. Preoperative mean scores for motor and bladder were 3.56 and 2.78 out of 5, 2.67 out of 4, and 2.11 out of 3 for bowel and sensory function, respectively. Postoperative mean score for motor, sensory, bladder, and bowel function revealed good neurological improvement. Statistically neurological improvement in bladder and bowel function was significant. More than 60% of patients had normal ambulation at follow-up. Conclusions: Patients presenting with recurrent symptoms in an operated case of SD need to be investigated, cause of recurrence has to be identified, and if needed repeat surgery is recommended at the earliest. Long-standing neurological deficits can potentially improve, especially bladder and bowel function which gives a good quality of life to the patients. Furthermore, we want to stress the fact that since it is an intradural pathology, these cases should be operated by experienced neurosurgeons, and this fact should be made aware among referring doctors.